Deep margin elevation: a systematic review - Z. S. Khabadze; I. V. Bagdasarova; E. S. Shilyaeva; A. P. Kotelnikova; D. A. Nazarova; Yu. A. Bakayev; S. M. Abdulkerimova (LLC "Endo Press", 2021)
Deep margin elevation (DME) is a nonsurgical, alternative technique of dental crown lengthening. Portion of direct restoration placed only at the deep apical part of the cavity to elevate the margin to a more coronal and more adequate position for final cementation of indirect restoration.Materials and methods. In this systematic review, we were looking for in vitro studies in which deep margin elevation (DME) technique were used. The electronic databases PubMed and EMBASE were used for the search. The search began on July 29, 2021 and ended on August 10, 2021. We have analyzed the materials and methods of each research and entered them in the appropriate tables to give a clearer assessment of the obtained results.Results. Analysis of marginal quality showed the best results when indirect restorations luted to dentin directly and with DME technique with three consecutive layers of resin composite. In groups without DME there were fewer microleakage. DME did not statistically significantly influence the fracture strength.Conclusions. We conducted a systematic review that included 12 in vitro studies. Even though samples without DME showed better results in in vitro studies, the difference between samples with and without DME was not statistically significant. However, in clinical practice, DME facilitates the insertion of indirect restorations. Therefore, further studies and clinical observations are necessary.